IMPLEMENTASI NILAI-NILAI PANCASILA DALAM PEMBENTUKAN KARAKTER CINTA DAMAI SISWA KELAS VI MADRASAH IBTIDAIYAH MAHAD AL-ZAYTUN - Atika Sholeha; Iis Humaeroh, Dadan Mardani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to describe the process of implementing Pancasila values, identify supporting and inhibiting factors in implementing Pancasila values, and analyze the impact of implementing Pancasila values on character formation of sixth grade students at Madrasah Ibtidaiyah Ma'had Al-Zaytun. This research method uses a qualitative descriptive approach with in-depth observation, interview, and documentation techniques for teachers and students in the 2024/2025 academic year, totaling 4 teachers and 6 students. A This study examines the implementation of Pancasila values in developing the peace-loving character of sixth-grade students at the Ma'had Al-Zaytun Elementary School. Pancasila values are implemented through daily activities such as communal prayer, mutual cooperation, group learning, and fair assignment distribution. A conducive school environment is a key supporting factor, while negative external influences such as social media act as obstacles. As a result, students demonstrate religious character, responsibility, respect for differences, and the ability to resolve conflicts peacefully.